Effect of Supplementation with Concentrate and Groundnut Haulm in Diets on milk yield of Dairy Azawak cows (International Journal of Scientific Research and Management (IJSRM), 2023)
An experiment was carried out to determine the effect of feeding diet containing concentrate and graded level of groundnut haulms (GH) on the milk yield of Azawak cattle. Five concentrate-groundnut mixed diets were formulated to contain on average 15% crude protein. The ratio concentrate to groundnut was 100:0; 67:33, 50; 50, 33:67 and 0:100 respectively. Twenty Azawak multiparous lactating cow aged 5-6 years and averagely weighing 317-320 kg were randomly divided into five groups of four animals each and were allotted to the five experimental diets in a randomized complete block design. Data were collected for Dry Matter Intake (DMI), Average Daily Intake (ADI), Average Daily Weight Gain (ADWG), Total Milk Yield, Average Milk yield and Feed conversion efficiency in milk (FCEM) throughout the three months experimental period. Results indicated that the average daily weight gain was higher on diet containing 50% inclusion of groundnut haulm in concentrate diet fed to Azawak cattle. The DMI by cattle was significantly (P˂0.05) higher on diet containing 67 and 100% groundnut haulm. The ADWG of lactating cows fed concentrate mixture was significantly higher on diet containing 33 and 50% inclusion levels but the feed conversion ratio was significantly higher at 50% level of groundnut haulm inclusion level. The total milk yield, average daily milk yield, the body score condition and the feed conversion efficiency in milk were not affected by the level of Groundnut haulms in the concentrate diets, but the highest values of these parameters were obtained at 50% inclusion level. It can be recommended that concentrate diet for Azawak cattle should be supplemented with 50% legume haulm for, better body score condition, feed conversion, feed conversion efficiency of milk and enhanced milk production during the long dry season.